P1 4 Pyramid of Geezers 2: Electric Boogaloo - Stainer, Alex; Jennings, John; Humphrey, Lili-Mair; Szczesniewski, Jakub (Physics Special Topics, 2024)
In this paper, we recalculate the theoretical maximum number of tiers in a human pyramid, originally calculated in a previous PST paper, using the ultimate compressive and yield strength of cortical bone. We found the maximum number of tiers to be between 8 and 10 before the ring metacarpal bone begins to yield and 14 to 17 before breakage.